Geomechanical evaluation of reservoirs in the coastal swamp, Niger delta region of Nigeria - Akpan Harry, Thomas; Edet Etuk, Sunday; Namdie Joseph, Inyang; Emeka Austin, Okoli (International Journal of Advanced Geosciences, 2018)
Evaluation of elastic parameters of reservoirs can be used in geomechanical modelling, wellbore stability analysis, and sanding, which can be applied in practical situation to optimize drilling, completion and productions of wells. Petrophysical analysis was done to identify various reservoirs in two wells, using sonic, neutron, gamma, resistivity and density logs. Porosity, Lithology and Water/Hydrocarbon saturation were determined. The lithology are mostly sand, shale and sandstone with sand/sandstone been the main lithology found in the reservoirs. Porosities in the two wells decreases with depth except in few cases, due to over pressured zones, caused by fluid contents. The reservoirs identified in the two wells are of economic importance due to their net pay zone ranging from 7.16m to 225.25m, with 1067m to 3507m depth, which is within the Agbada formation, having a minimum an average hydrocarbon saturation of 50%. Elastic parameters evaluated are Vs, Vp, Vp/Vs, Poisson ratio, Shear Impedance, Acoustic Impedance, Bulk Modulus, Shear Modulus and Young Modulus. Vp/Vs and Poisson ratio was used to also infer and confirm the lithology gotten from gamma log and also used to discriminate between, oil sand, gas sand and brine sand. The Elastic properties of the reservoirs that are found mostly in the sandstone lithology varies between 15437.91 to 31522.28psi, 7.10 to 24.78Kbar, 5929.51 to 22339.26psi, 1.94 to 18.06Kbar, 1.70 to 2.31, 5.34 to 43.59psi of Acoustic Impedance, Bulk Modulus, Shear Impedance, Shear Modulus, Velocity ratio and Young Modulus respectively.Â Â